(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article examines the theoretical and methodological foundations of ethnocultural tourism and its structural components. The study provides a comparative analysis of tourism concepts based on international and Uzbek experiences. Special attention is given to the classification of tourism types, the role of cultural heritage, and the integration of ethnocultural tourism into regional development strategies. The research employs comparative, analytical, and system-based approaches, supported by tables and scientific interpretations.